IgG4-related disease with massive pericardial effusion diagnosed clinically using FDG-PETCT: a case report - Wei, Qiaofeng; Qi, Huili; Wei, Hongmei; Wang, Xiuhua; Zhang, Hongju (Frontiers in Immunology, 2023)
Background: IgG4-related disease (IgG4-RD) is a systemic inflammatory disease which involves various organs such as the pancreas, lacrimal gland, salivary gland, retroperitoneum, and so on. These organs can be affected concomitantly. 18-Fluorodeoxyglucose positron emission tomography computed tomography (FDG-PETCT) is a systemic examination which can identify active inflammation and detect multiple organ involvement simultaneously. Pericardial involvement is rare in IgG4-RD, early detection and treatment can greatly improve the prognosis of patients.